2009
DOI: 10.1111/j.1756-185x.2009.01378.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteitis condensans ilii: a significant association with sacroiliac joint tenderness in women

Abstract: Aim: To determine whether subjects with radiological evidence of osteitis condensans ilii exhibit symptoms and signs in common with sacroiliitis when compared with an age-matched control group and to examine demographic features. Methods:The Dunedin Hospital radiology database was searched for all subjects with changes of osteitis condensans ilii over a 10-year period. An age-matched control group with plain X-rays of the pelvis was recruited from the same database. All subjects were sent a questionnaire enqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 9 publications
2
20
0
Order By: Relevance
“…This condition is most commonly observed in women who have had a previous pregnancy, although it can still be observed in nulliparous women [20,21]. The onset of pain is during the pregnancy or the postpartum period.…”
Section: Osteitis Condensans Iliimentioning
confidence: 95%
“…This condition is most commonly observed in women who have had a previous pregnancy, although it can still be observed in nulliparous women [20,21]. The onset of pain is during the pregnancy or the postpartum period.…”
Section: Osteitis Condensans Iliimentioning
confidence: 95%
“…On physical examination, focal tenderness over the sacroiliacal joints and during compression tests can be observed. 5,6 Also patients may have increased lumbar lordosis, moderate obesity, and lumbar extensor muscle spasm. 1 There are no neurologic deficit symptoms or signs.…”
Section: Figurementioning
confidence: 99%
“…These results were all comparable with previously reported large series of OCI. [3][4][5]8,14 Four cases (14.8%) were HLA-B27 antigen positive (two cases demonstrating BME and two cases not). This seems higher than most literature reports, but was comparable with Singal et al 4 who reported the distribution of HLA-B27 antigens in a group of 37 female patients; four of the 25 OCI patients (16%) were B27 positive while 11 of 12 ankylosing spondylitis patients (92%) were B27 positive.…”
Section: Discussionmentioning
confidence: 99%